2019
DOI: 10.1002/mawe.201800141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of yttrium oxide in hydroxyapatite/aluminum oxide hybrid biocomposite materials: Phase, mechanical and morphological evaluation

Abstract: This study presents the fabrication and characterization of composite materials of hydroxyapatite and aluminum oxide. Hydroxyapatite powder was obtained from bovine bones via conventional calcination routine. Although hydroxyapatite shows great biocompatibility with the human body, its applications are limited to non-load bearing areas. For this purpose, fine powders of hydroxyapatite/alumina were admixed with 1 and 5 wt.% yittria. Powder-compacts were sintered by two-step sintering route by increasing tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…In 2019 Özer and Öksüz concluded that the adding of yttrium in biocomposite causes the formation of glassy phases, which encourages the grain boundary migration and, because of the high diffusion rate, seals the open pore structure. 7 Electrical investigations.-The results for the pure HA matrix will be presented to analyze the effect of sintering temperatures on dielectric characteristics and electrical conductivity due to the influence of integrated Y 2 O 3 in HA. The results of the two nanocomposites will be, in comparison with the effect of the Y 2 O 3 ratio as measured by XRD and FT-IR taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019 Özer and Öksüz concluded that the adding of yttrium in biocomposite causes the formation of glassy phases, which encourages the grain boundary migration and, because of the high diffusion rate, seals the open pore structure. 7 Electrical investigations.-The results for the pure HA matrix will be presented to analyze the effect of sintering temperatures on dielectric characteristics and electrical conductivity due to the influence of integrated Y 2 O 3 in HA. The results of the two nanocomposites will be, in comparison with the effect of the Y 2 O 3 ratio as measured by XRD and FT-IR taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they admixed fine powders of HA/alumina with 1 and 5-wt% yttria. 7 To the best of our knowledge, there are numerous reports on HA but limited on sintered HA/Y composites.…”
mentioning
confidence: 99%
“…Thirty-two indents were made per region (outer/inner surface) for each mussel shell, and the data are presented as mean ±standard deviation (SD). The distribution of the Vickers microhardness values for the outer layer and inner layer was characterized and discussed (Özer and Öksüz, 2019;Yang et al, 2011).…”
Section: Vickers Microhardness (Hv) Experimentsmentioning
confidence: 99%